Post-Pandemic Language Development Delays in Indonesia Preschoolers: Digital Exposure Challenges and SDGs 4 Implementation - Imelda Wahyuni; Noni Putri; Muhammad Shaleh Assingkily; Henny Septia Utami; Khoirunnisa Khoirunnisa (Journal of Contemporary Islamic Primary Education, 2025)
Despite extensive research on early childhood language development, significant gaps remain in understanding how pandemic-induced social isolation combined with excessive digital exposure affects language acquisition in developing countries. This study examines language development challenges among Indonesian children born 2020-2023 (post-COVID cohort) and implications for Sustainable Development Goal 4 achievement. Using descriptive qualitative methodology, we conducted semi-structured interviews with 24 early childhood educators and 36 parents across six Indonesian provinces, complemented by systematic classroom observations. Thematic analysis revealed three critical challenges: articulation delays affecting 73% of observed children, functional vocabulary deficits 40-50% below pre-pandemic norms, and severe communication confidence impairments. Pandemic-era social restrictions during critical language development periods, combined with unsupervised device usage exceeding four hours daily, emerged as primary determinants. However, intensive parental verbal engagement demonstrated significant protective effects. These findings challenge assumptions that digital tools adequately substitute human interaction in language learning contexts. This research contributes evidence-based frameworks for post-pandemic early childhood education policy, emphasizing oral interaction restoration as fundamental to SDG 4 implementation in Indonesia's digital transformation era.